(untitled) (International conference on multidisciplinary science, 2025)
This thesis examines the semantic analysis of adjectives in the Uzbek language and their representation in a computational thesaurus. Adjectives, essential for expressing qualities and states, are analyzed through tools like word embeddings and corpus-based methods. The study highlights the semantic clustering of synonyms and the disambiguation of polysemous adjectives, ensuring their accurate organization in a thesaurus. Challenges such as contextual ambiguity and incomplete resources are addressed using computational techniques complemented by expert linguistic input. The research underscores the value of visualization and computational tools in creating intuitive and effective linguistic resources. This approach enhances applications in natural language processing, education, and linguistic research while preserving the richness of the Uzbek lexicon.